Hope Labor: The Role of Employment Prospects in Online Social Production - Kuehn, Kathleen; Corrigan, Thomas F (The Political Economy of Communication, 2013)
This research introduces 'hope labor' as a motivation for voluntary online social production, defined here as 'un- or under-compensated work carried out in the present, often for experience or exposure, in the hope that future employment opportunities may follow'. Drawing from interviews with SB Nation sports bloggers and Yelp consumer reviewers, this research expands current understandings of the motivations behind online social production. Structurally, we distinguish hope labor from other forms of free labor by emphasizing the temporal relationship between present and future work–a relationship that shifts costs and risks onto the individual. Hope labor is naturalized and normalized through neoliberal ideologies. It is seen as an investment that pays off for individuals based on merit, despite its deleterious impact on employment prospects in desired industries. Our theorization of hope labor can be seen as a complement or corrective to celebratory accounts of meaning making, creativity, and community in online social production.